VD_FINDINFO HC / 2013 / 367 vom 29. Mai 2013 - VD Tribunal cantonal (2013)
MESURE PROVISIONNELLE, CONJOINT, ENFANT, DIVORCE, MODIFICATION DES CIRCONSTANCES | 176 al. 1 ch. 1 CC, 179 al. 1 CC, 276 al. 1 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH)